Evaluation of mobile applications in foreign language learning at early age - Davudova, Enejan; Türel, Yalın Kılıç (Gürhan DURAK, 2022)
In the technology era that we are in, teaching with traditional method is not sufficient alone in increasing efficiency. Varied content, whether technological or not, has an important place to increase the effectiveness of teaching. The methods and models used in the selection and usage of these contents are also considered important in terms of achieving the targeted success. In this study, the effects of mobile applications used in foreign language learning were examined on students' academic achievement. A total of 87 students from the Experiment-1 (E1), Experiment-2 (E2) and Control (C) groups consist of the sampling of this study. The English Achievement Test (EAT) was applied to all three groups as pretest and posttest. C group has attended to the regular face-to-face classroom teaching while students in E1 and E2 groups additionally used Duolingo and Memrise, respectively. In addition, volunteer parents and students’ opinions about mobile applications were received after the implementation. In line with the results obtained by comparing the groups with respect to each other, it was concluded that the E2 group obtained higher scores from EAT than the E1 and C group. Particularly, there is a higher increase in the average score in the "Reading and Writing" section of the E2 group. According to the opinions of students and parents, both applications can be said to improve academic success positively.
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar